Hedging cross border commodity price risk - Varma, Jayanth (London : SAGE Publications Ltd, 2017)
The case is about an Indian company hedging soya oil price risk in the US futures market instead of in the Indian market to take advantage of better liquidity and wider choice of hedging instruments there. A stable long run relationship (cointegration) between the two markets appeared to make the cross border hedge viable, but hedge accounting considerations appeared to stand in the way.
Originally published: Varma, J. (2013). Hedging cross border commodity price risk. F&A0509. Ahmedabad: Indian Institute of Management, Ahmedabad.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Soybean industry -- India -- Case studies; Soybean industry -- United States -- Case studies; Hedging (Finance) -- India -- Case studies; Hedging (Finance) -- United States -- Case studies; Commodity futures -- India -- Case studies; Commodity futures -- United States -- Case studies